A study to assess knowledge and attitude towards HIV among students from Mumbai university - Limaye, Dnyanesh; Fortwengel, Gerhard; Limaye, Vaidehi; Bhasi, Aishwarya; Dhule, Aditya; Dugane, Rajesh; Borkar, Asang; Pitani, Ravi Shankar; Sathe, Sushama; Kapadi, Atul (International Journal of Research in Medical Sciences, 2019)
Background: India has the third largest HIV epidemic in the world. The Indian epidemic is characterized by low levels in the general population and elevated concentrations among high-risk groups. The present study was planned to determine the awareness of HIV among students from Mumbai University. Methods: A cross-sectional study was carried out among students from Mumbai University, India during May–June 2017. Two hundred and fifty students were approached to participate in the study of which 199 agreed to participate (males: 132; females: 67). Pretested questionnaire was distributed and collected data was analyzed using IBM SPSS version 23. Results: Study participants had high knowledge (86%) and attitude score (87%). There was no significant difference between males and female participants for attitude and knowledge, except for one question regarding knowledge about HIV transmission via breastfeeding to child. Conclusions: Present study showed that there are no misconceptions or negative attitudes regarding HIV among students. A longitudinal study with a larger sample size across India is recommended for further investigation.